2019
DOI: 10.3348/kjr.2018.0742
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Radiologic Extranodal Extension in Human Papillomavirus-Related Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective To determine whether radiologic extranodal extension (ENE) appearing on pretreatment CT and MRI could predict the prognosis in patients with human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC). Materials and Methods The study population was obtained from a historical cohort diagnosed with HPV-related OPSCC. A total of 134 OPSCC patients who had a metastatic lymph node on pretreatment CT or MRI were included, and radiologic ENE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…P16 immunohistochemistry or HPV DNA detection by polymerase chain reaction (PCR) was used as the reference standard 35,36 . P16 immunohistochemistry was performed using CINtec p16 histology (anti-p16 INK4a mouse monoclonal antibody and immunohistochemical detection kit; Roche MTM Laboratories, Heidelberg, Germany) and HPV DNA detection was performed by 16,18,31,33,35,39,45,51,52,56,58,59,68,73,82, and other lower or undetermined risk subtypes) 37 . HPV-positive OPSCC was diagnosed based on the positive results of either p16 or HPV DNA PCR 38 .…”
Section: Study Populationmentioning
confidence: 99%
“…P16 immunohistochemistry or HPV DNA detection by polymerase chain reaction (PCR) was used as the reference standard 35,36 . P16 immunohistochemistry was performed using CINtec p16 histology (anti-p16 INK4a mouse monoclonal antibody and immunohistochemical detection kit; Roche MTM Laboratories, Heidelberg, Germany) and HPV DNA detection was performed by 16,18,31,33,35,39,45,51,52,56,58,59,68,73,82, and other lower or undetermined risk subtypes) 37 . HPV-positive OPSCC was diagnosed based on the positive results of either p16 or HPV DNA PCR 38 .…”
Section: Study Populationmentioning
confidence: 99%
“…Pretreatment imaging has a low sensitivity for detection of ENE, with reported sensitivities of 50% to 60%. 59,60 Extranodal extension is a poor prognostic factor in HNSCC. 61,62 In HPV-associated oropharyngeal cancer, it is considered a relative contraindication for TOS since patients with ENE will require adjuvant chemoradiation.…”
Section: Pathological Findings Based On Imagingmentioning
confidence: 99%
“…Sensitivity and specificity of predicting ECE on CT in patients with HPV+ OPSCC range from 43.7% to 65% and from 54% to 97.7% respectively, whereas those of MRI range from 57% to 77% and from 57% to 72%, respectively. [19][20][21] Radiologic examination of ECE in preoperative PET/CTs of our patient population demonstrated poor accuracy in comparison to pathologic examination and poor interrater reliability between radiologists (κ = 0.403). These results indicate that PET/CT is not a reliable indicator of ECE in patients with HPV+ OPSCC.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have shown that ECE may not be a significant prognosticator of HPV+ OPSCC. 23,24 The decision to employ surgical versus nonsurgical treatment critically relies on the severity of nodal disease, T classification, and ECE. With adequate surgical exposure and anatomical favorability for a complete resection, surgical approach can spare the patients a potentially avoidable adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%